Role of physical activity in the occurrence of falls and fall-related injuries in community-dwelling adults over 50 years old - Pereira, Catarina (2015)
Purpose: This study examined the effect of the type, level and amount of physical activity in falls and fall-related injuries. Method: Participants were 506 community-dwelling adults aged >50 years (390 women: 67.7 ± 6.8 years and 116 men: 69.6 ± 6.6 years). Falls, fall-related injuries (slight and severe), and physical activity (type, level and energy expenditure) were evaluated by questionnaires. Confounders included co-morbidities, fear of falling, environmental hazards and physical fitness. Results: After adjustment for confounders, logistic analysis revealed that the likelihood of falling decreased by 2% for each 100 metabolic expenditure (MET-min/week) of total physical activity and increased by 5% for each 100 MET-min/week of vigorous-intensity physical activity; total physical activity >1125 MET-min/week and vigorous physical activity <500 MET-min/week were identified as cut-off values discriminating non-fallers from fallers. Compared to the low physical activity level, increased physical activity levels diminished the likelihood of the occurrence of severe fall-related injuries by 76% (moderate) and 58% (high; p < 0.05) in fallers. Conclusions: Being active, especially sufficiently active, reduces fall-related injuries by decreasing falls and by safeguarding against severe injuries when falls occur. At least 1125 MET-min/week of total physical activity including >500 MET-min/week of vigorous intensity seems to prevent falls and, therefore, fall-related injuries.